The Desire to Become a Chosen Woman in Sěrāt Mějang Dhatěng Garwa R.P. 366.45 - Rahayu, Wiwien; Hernawan, Vighna (Sutasoma : Jurnal Sastra Jawa, 2025)
Sufism as a divine teaching is present in various Javanese literary works, one of which is Serat Mejang Dhateng Garwa R.P. 366.45, a macapat text that is part of the serat piwulang, containing the advice of a father to his daughter. Despite its didactic nature, this text is rich in Sufi values that guide women as active subjects toward the perfection of life and closeness to the Divine. This process of inner education aligns with the concept of suluk or the spiritual journey toward God, giving the text a spiritual didactic dimension. This study aims to understand how the father's advice to his daughter is conveyed, the strategies used, and how women are positioned as chosen figures. The research method used is qualitative with a Lacanian psychoanalytic approach to gender. The results show that in the text, the song serves as a medium for conveying messages; women are positioned as subjects who recognize their shortcomings to fulfill their spiritual needs. The title represents the symbolic relationship between the prologue (husband) and the content (wife). At the same time, the daughter as a subject relates directly to the mother and indirectly to the father. This text represents Sufi values and gender awareness within the aesthetics of macapat.